2023
DOI: 10.1371/journal.pone.0289711
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice (KAP) of antimicrobial prescription and its resistance among health care providers in the COVID-19 era: A cross sectional study

Abstract: Antimicrobial resistance (AMR) is considered as a global health and development threat. During COVID-19 pandemic, there has been an increase in antimicrobial resistance. Health care providers (HCPs) play the main role in facing antibiotic resistance because they have the authority to prescribe antibiotics during clinical practice as well as in promoting patients’ compliance with therapies and avoid self-medication. So, this study will serve as an important source of information in context with Covid19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…In the current survey investigation, it was found that selfemployed individuals exhibit a commendable understanding (41.8%) of AMR and the One Health Approach policy. This finding stands in opposition to the research conducted by Nemr et al, which contradicts their conclusion that healthcare providers possess a significantly higher level of knowledge (93.7%) concerning antibiotic prescription and resistance [23]. It is widely acknowledged that health care providers play a crucial role in maintaining a robust health system [24].…”
Section: Resultsmentioning
confidence: 75%
“…In the current survey investigation, it was found that selfemployed individuals exhibit a commendable understanding (41.8%) of AMR and the One Health Approach policy. This finding stands in opposition to the research conducted by Nemr et al, which contradicts their conclusion that healthcare providers possess a significantly higher level of knowledge (93.7%) concerning antibiotic prescription and resistance [23]. It is widely acknowledged that health care providers play a crucial role in maintaining a robust health system [24].…”
Section: Resultsmentioning
confidence: 75%